2016
DOI: 10.1001/jamaoncol.2016.1279
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of ESR1 Mutations in Cell-Free DNA and Outcomes in Metastatic Breast Cancer

Abstract: IMPORTANCE Estrogen receptor α (ESR1) mutations found in metastatic breast cancer (MBC) promote ligand-independent receptor activation and resistance to estrogen-deprivation therapy in laboratory models. The prevalence of these mutations and their potential impact on clinical outcomes has not been established. OBJECTIVE To determine the prevalence of ESR1 mutations (Y537S and D538G) in estrogen receptor (ER)-positive MBC and determine whether mutation is associated with inferior outcomes. DESIGN, SETTING, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
393
1
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 418 publications
(444 citation statements)
references
References 15 publications
23
393
1
11
Order By: Relevance
“…The recent discoveries of hotspot ER mutations in metastatic breast cancer further strengthen the key role of ER in drug resistance and disease development. The recurrent mutations, mainly occurring on tyrosine-537 and aspartic acid-538 located in the ligand-binding domain, are enriched in nearly 30% of endocrine-therapy resistant metastases and are associated with more aggressive disease biology with shorter overall survival relative to the wild-type ER [13]. Furthermore, ER mutations induce ligand-independent activation of the ER pathway and confer partial resistance to existing classes of endocrine therapies [7][8][9][10][11][12][13]30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent discoveries of hotspot ER mutations in metastatic breast cancer further strengthen the key role of ER in drug resistance and disease development. The recurrent mutations, mainly occurring on tyrosine-537 and aspartic acid-538 located in the ligand-binding domain, are enriched in nearly 30% of endocrine-therapy resistant metastases and are associated with more aggressive disease biology with shorter overall survival relative to the wild-type ER [13]. Furthermore, ER mutations induce ligand-independent activation of the ER pathway and confer partial resistance to existing classes of endocrine therapies [7][8][9][10][11][12][13]30].…”
Section: Discussionmentioning
confidence: 99%
“…The hotspot mutations in ER, which are enriched in nearly 30% of endocrine therapy-resistant metastases, induce ligand-independent activation of the ER pathway [7][8][9][10][11][12], confer partial resistance to existing classes of endocrine therapies, and are associated with more aggressive disease biology with shorter overall survival in patients relative to the wild-type ESR1 [13].…”
Section:  mentioning
confidence: 99%
“…Gain-of-function mutations in ESR1, the gene encoding the ER, are a relatively rare event in primary breast cancer (Cancer Genome Atlas Network 2012), but can be detected using next-generation sequencing in approximately 20% of patients with metastatic ER-positive disease who had received prior endocrine therapies , Toy et al 2013, Jeselsohn et al 2015. A higher prevalence (up to 55%) of ESR1 mutations has been reported in circulating free DNA (cfDNA) in metastatic ER-positive breast cancers with prior AI therapy when using digital droplet PCR to increase mutation detection sensitivity (Chandarlapaty et al 2016, Fribbens et al 2016, Spoerke et al 2016. These mutations cluster in the ligand-binding domain of the ER and lead to ligand-independent ER activity that promotes tumour growth, partial resistance to endocrine therapy and potentially enhanced metastatic capacity.…”
Section: Endocrine-related Cancer (2016) 23 T227-t241mentioning
confidence: 99%
“…Additionally, recent digital PCR assays on plasma cell-free DNA (cfDNA) of several cohorts demonstrated the difference in the clinical features between the representative hotspot mutations in MBC, PIK3CA and ESR1 mutations [6][7][8][9][10]. In the BOLERO-2 study, Chandarlapaty and colleagues demonstrated that progression free survival (PFS) benefit of mammalian target of rapamycin (mTOR) inhibitor everolimus was maintained irrespective of PIK3CA mutations, but that was decreased according to the presence of ESR1 mutations [6,7]. In another two phase III randomized trials, Fribbens and colleagues reported the effectiveness of the target drug by having the mutations or not.…”
mentioning
confidence: 99%